Primary Cutaneous Amyloidoma: A Case Report - Julia García Reitboeck; Robert Feldmann; Dagmara Loader; Friedrich Breier; Andreas Steiner (Karger Publishers, 2014)
Amyloidoma is defined as solitary, localized, tumor-like deposit of amyloid in diverse organs without evidence of systemic amyloidosis. Here we report the case of a 49-year-old male patient with a solitary amyloidoma of the skin seated on the left upper lip. Full medical examination showed no signs of systemic amyloidosis. The mass was removed surgically with tangential shave and so far no signs of recurrence have been found.